Mediating Alghorithm Mediating Da’wa: The New Preacher and Optimization of Social Media for Da’wa in the Case of Habib Ja’far - Fitriansyah, Nuzul; Lubis , Torkis (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
persist regarding the depth and credibility of social media-based da’wa, often perceived as superficial and lacking religious authority. This study investigates the case of Habib Husein Ja’far Al-Hadar, a traditionally trained Hadhrami preacher, who has emerged as a prominent digital da’i through his strategic and effective use of Instagram, TikTok, Twitter, and YouTube. The research aims to explore how algorithmic logic, media constraints, and digital culture shape and potentially enhance the reach and substance of da’wa in contemporary Indonesia. Anchored in digital ethnography and qualitative content analysis, the study draws upon online observations and platform analytics to examine how Habib Ja’far optimizes message delivery across social media, navigating technical limitations to convey inclusive, youth-oriented Islamic messages. Findings reveal that beyond religious qualifications, digital fluency—understanding algorithms, audience behavior, and platform affordances—is essential to successful digital da’wa. Habib Ja’far’s approach demonstrates how algorithmic literacy and creative communication can challenge the dichotomy between traditional and modern religious authority. This research contributes to broader discussions on mediatized religion, digital religious authority, and the transformation of Islamic communication in the algorithmic age.